2009
DOI: 10.1080/09084280902864485
|View full text |Cite
|
Sign up to set email alerts
|

Malingering Intellectual Disability: The Value of Available Measures and Methods

Abstract: Atkins v. Virginia (2002) is a case that has changed the landscape in relation to the assessment of malingering in a legal context. This landmark decision abolished the death penalty for defendants found to have intellectual disability (ID; formally known as mental retardation), but limitations in our assessment techniques lead to questions regarding the veracity of ID claims. In fact, Justice Scalia noted with clarity that concerns exist regarding the ability of individuals to feign ID and to do so successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…As there is always concern that truly-impaired individuals will fail symptom validity testing (Salekin & Doane, 2009), particularly if the test is highly sensitive, the methods of Howe and Loring (2009) were used to refine the definition of failure on the MSVT. In particular, individuals who are truly impaired will satisfy the requirements for a Dementia Profile (Green, 2004;Howe & Loring, 2009), subsequently characterized as a ''severely impaired'' profile by Carone (2009): (1) failure (590%) on a symptom validity indicator (IR, DR, or Con); (2) no scores significantly below chance (530%); (3) at least a 20-point difference between the mean of the easy tests (IR, DR, and Con) and the mean of the hard tests (PA and FR): Easy4Hard by at least 20 points; (4) IR and DR are greater than FR; and (5) PA4FR.…”
Section: Medical Symptom Validity Test (Msvt) the Medical Symptom Vamentioning
confidence: 99%
See 1 more Smart Citation
“…As there is always concern that truly-impaired individuals will fail symptom validity testing (Salekin & Doane, 2009), particularly if the test is highly sensitive, the methods of Howe and Loring (2009) were used to refine the definition of failure on the MSVT. In particular, individuals who are truly impaired will satisfy the requirements for a Dementia Profile (Green, 2004;Howe & Loring, 2009), subsequently characterized as a ''severely impaired'' profile by Carone (2009): (1) failure (590%) on a symptom validity indicator (IR, DR, or Con); (2) no scores significantly below chance (530%); (3) at least a 20-point difference between the mean of the easy tests (IR, DR, and Con) and the mean of the hard tests (PA and FR): Easy4Hard by at least 20 points; (4) IR and DR are greater than FR; and (5) PA4FR.…”
Section: Medical Symptom Validity Test (Msvt) the Medical Symptom Vamentioning
confidence: 99%
“…The Social Security Administration (SSA) has had many concerns about the programmatic use of SVTs, particularly as the claimants are low-functioning (Chafetz, 2010). From a different point of view concerning criminal defendants who might have mental retardation, Salekin and Doane (2009) have criticized the simplistic use of SVTs when evidence exists that lower-functioning individuals may have higher false-positive rates of SVT failure. However, as Chafetz et al (2007) have shown, claimants for Social Security Disability have meaningful correlations between effort and IQ, and thus without SVTs it becomes exceedingly difficult to delineate poor effort from truly-impaired intellectual difficulties, which may provide evidence for a disability decision.…”
Section: Reducing False Positives In Malingering 1247mentioning
confidence: 99%
“…In Atkins cases, the primary validity concern is misclassification, essentially opining that a defendant's results are invalid due to poor effort quality, when in fact the suboptimal PVT scores are due to veritable intellectual deficits. Specificities of PVTs in low IQ samples are mixed, with some studies demonstrating sufficient specificity (Brockhaus & Merten, 2004 (2007), Shandera et al (2010), and Salekin and Doane (2009). Salekin and Doane (2009) have also criticized the use of PVTs in MR/ID individuals due to their development and norming in higher IQ individuals.…”
Section: Criticism Of Performance Validity Testing In Capital Casesmentioning
confidence: 99%
“…Specificities of PVTs in low IQ samples are mixed, with some studies demonstrating sufficient specificity (Brockhaus & Merten, 2004 (2007), Shandera et al (2010), and Salekin and Doane (2009). Salekin and Doane (2009) have also criticized the use of PVTs in MR/ID individuals due to their development and norming in higher IQ individuals. This particular criticism pertains to the relevance of these tests in low IQ individuals, which may be considered as a Daubert issue.…”
Section: Criticism Of Performance Validity Testing In Capital Casesmentioning
confidence: 99%
“…The problem with use of such measures with low-IQ people, as pointed out in a review by Salekin and Doane (2009), is that the assumption of automaticity of the tasks is not really proven for low-IQ individuals, and thus low ability and low effort are often confounded. A related problem is that low effort is sometimes inferred indirectly from the amount of time taken on the assumption that a long latency on such an easy task must be indicative of deliberation about how to fake.…”
Section: Possible ''Malingering''mentioning
confidence: 99%